2007
DOI: 10.1063/1.2709740
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigations of Co- and Fe-doped SnO2

Abstract: We have investigated the electronic and magnetic properties of Co- and Fe-doped SnO2 by first-principles methods. The obtained results show that the ferromagnetic order is energetically much favored relative to the antiferromagnetic order in all the considered models of Co- and Fe-doped SnO2. The exchange interaction between Co ions is a long-range ferromagnetic interaction and gradually weakened as the distance between Co ions increases. For Fe-doped SnO2, the exchange interaction is also a long-range ferroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
5
25
0
Order By: Relevance
“…Tin dioxide layers doped with antimony or iron ions are used in electroluminescent devices [6,7]. Doping a small amount of a transition metal (Fe, Cr, Co, Ni, V) into non-magnetic oxides could induce room temperature ferromagnetism, indicating the potential of such systems for spintronic applications [8][9][10][11][12][13][14][15][16]. Combinations of various semiconductors (SnO 2 , TiO 2 , ZnO) and noble metals (Ag, Au, Pd and Pt) boost photocatalytic activity by trapping photo-induced charge-carriers and improving charge transfer process [1-3, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Tin dioxide layers doped with antimony or iron ions are used in electroluminescent devices [6,7]. Doping a small amount of a transition metal (Fe, Cr, Co, Ni, V) into non-magnetic oxides could induce room temperature ferromagnetism, indicating the potential of such systems for spintronic applications [8][9][10][11][12][13][14][15][16]. Combinations of various semiconductors (SnO 2 , TiO 2 , ZnO) and noble metals (Ag, Au, Pd and Pt) boost photocatalytic activity by trapping photo-induced charge-carriers and improving charge transfer process [1-3, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The ab initio calculations for the (TM) x Sn 1-x O 2 (TM= V, Mn, Fe and Co) were performed [1][2][3], and it was concluded that ferromagnetic moments appeared for Fe, Co, but not for V and Mn. In the study by our group [4], the TM oxides (V 2 O 5 , VO 2 Except for the TM-doped SnO 2 , the room temperature ferromagnetism, induced by the oxygen vacancies, has been reported for SnO 2 thin films, nano-particles and nano-wires [5][6][7][8]. As for the SnO 2 nano-particles [6], the sample preparations were performed by chemical reaction between organic solvent and metal nitrate.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, several computational investigations have been reported on the magnetic properties of TM-doped SnO 2 [28][29][30][31]. Wang et al studied the electronic structure and magnetic properties of Co-doped SnO 2 by first-principle calculations [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied the electronic structure and magnetic properties of Co-doped SnO 2 by first-principle calculations [28,29]. However, the influence of oxygen vacancies on the exchange interaction between separated Co spins has not been investigated and atoms relaxation is not performed in the calculation.…”
Section: Introductionmentioning
confidence: 99%